تجليات الإقليمية الحديثة في البلدان النامية ، الأنماط والأساليب. - نصرة, ميرنا; سعيد, نسيبة (Latakia University Journal -Engineering Sciences Series, 2019)
بدأت المدن في البلدان النامية – وبحلول أوائل الستينات من القرن العشرين- بالنمو وفق الشكل العالمي بعيداً عن الانتماء المكاني المحلي ،وانتشرت التصاميم المعمارية الدولية الحديثة بأشكالها وتصاميمها المكررة ، الأمر الذي أدى إلى إشكاليات هامة أثرت في الأماكن التي وجدت فيها وقدمت إشكالات مضافة كإشكالية الانفصال بين النماذج الغربية المقتبسة والقيم القومية ، وإشكالية تنامي ظاهرة عمارة العولمة التي تهتم فقط بإعلاء النواحي الشكلية. شكلت الإقليمية الحديثة في السنوات القليلة الماضية حلاً للنقاش المتزايد في الدول النامية حول حالة العمارة والعمران ، في محاولة من المعماريين والمخططين لتأمين الانتماء والمواءمة مع المكان وسعياً لمواجهة مفهوم اللامكان في العمارة الحديثة ، باستخدام المعطيات السياقية لإعطاء معنى وروح للمكان، وفق إعادة النظر في إمكانية الاستفادة من معطيات الموقع من مواد بناء وتقنيات ومناخ وطبيعة ، إضافة إلى الموروث الثقافي . Cities begun in developing countries, by the earlier sixties of the 20th century, to grow according to the world pattern away from local and locative Affiliation. Also architectural modern international designs started to spread among its repeated shapes and designs. Such a thing led to important issues that affected places where it was found and presented more issues such as the separation between western adapted patterns and national values, and the issue of development of the Phenomenon of Globalization architecture which is only interested in upholding formalism aspects. Modern regionalism formed in the last few years a solution of the growing debate in the developing countries about the situation of the architecture and urbanism, in an attempt by the architects and planners to provide the affiliation and alignment with the place, and in order to cope with the concept of nowhere in modern architecture using sequenced data to provide meaning and spirit to the place. Accordingly, to reconsider the possibility of making use of the location data of the building such as building materials, techniques, climate and nature, as well as cultural, civilized and community heritage, including its content of the customs and traditions and re-interpreted within the concept of modernity, the concept that has gained a strong and comprehensive presence in the first half of the twentieth century and that was in the aim of finding authentic formulas within modernity.